Enhanced gentamicin loading and release of PLGA and PLHMGA microspheres by varying the formulation parameters - Chaisri W. (2014)
The purpose of this study was to develop a suitable formulation for gentamicin sulfate (GS) that gives a sustained release of the drug. Therefore this drug was loaded into poly(d,l-lactide-co-glycolide) (PLGA) and poly(lactic-co-hydroxymethyl glycolic acid) (PLHMGA) microspheres. The effects of various formulation parameters (ethanol, surfactant, osmotic value of the external phase, polymer type and concentration) on particle characteristics (size, loading and release) were investigated. The GS loaded microspheres were prepared using a double emulsion evaporation technique. The results demonstrate that neither ethanol nor surfactants had beneficial effects on the drug loading efficiency (around 4-10%). However, an increase in buffer concentration (and thus osmotic pressure) of the external phase resulted in a substantial increase of GS-loading (from 10 to 28%). Further, an increase of concentration of PLGA in DCM from 10% to 15/20% caused a 4-time increase of the drug loading. The best formulation identified in this study had a loading efficiency of around 70% resulting in PLGA microspheres with a 6% (w/w) loading. The particles showed a burst release of the drug depending on their porosity, followed by a phase of 35. days where hardly any release occurred. The drug was then slowly released for around 25. days likely due to degradation of the microspheres. The drug loading efficiency of GS in PLHMGA was not significantly different from PLGA microspheres (64%). The release of GS from PLHMGA microspheres was faster than that of PLGA because the degradation rate of PLHMGA is more rapid than PLGA. This study shows that prolonged release of gentamicin can be obtained by loading this drug into microspheres made of biodegradable aliphatic polyesters. © 2011.